Encouraging a 'Barrier-free Built Environment' in a Malaysian University - Hussein, H. (Faculty of Built Environment, University of Malaya, 2005)
A good pedestrian network around the campus should be accessible and friendly for all users including disabled persons. The environment should offer some activity nodes to ensure that the learning and working in campus is more pleasant. The paper will clarify the importance of collaborative development among various professionals and organisations in order to achieve a 'barrier-free built environment', focusing on the University of Malaya as a case study. It will share experience on the education of inclusive design for students who will become professionals and responsible in implementing the legislation relating to safety, accessibility and usability of the built environment. As the objective is the issue of educating relevant professionals, it will introduce methods in teaching professionals as a strategy to advocate a 'barrier-free built environment'. The paper will also illustrate the efforts done in encouraging the agenda which have been implemented around the case study.